STUDENTS' PERCEPTIONS ON THE INSTRUCTIONAL MEDIA USED BY TEACHER IN TEACHING ENGLISH - Abubakar, Multazam; Alfian, Wahyu; Rasyid, Muhammad Akbar Nur (Universitas Aisyah Pringsewu, 2023)
This study aims to find out the media used by the teachers in teaching English at SMPN 9 Selayar and to investigate the students’ perception of the instructional media used by the English teachers in teaching English at SMPN 9 Selayar. A quantitative approach using the descriptive method was employed in this study to investigate students’ perceptions on the instructional media used by teachers in teaching English, while the research instruments were observation, questionnaires, and documentation. This study found that three types of learning media are often used by teachers in teaching English namely English books, whiteboards, and dictionaries. The kinds of media that the teacher used when teaching English were a whiteboard, an English book, and a dictionary. Most of the students gave a positive perception toward the media used by English teachers in the teaching and learning process, they were being happy, more active, being more excited/spirit in learning English, they were easier to understand the materials, they can improve their pronunciation, vocabulary, find new ideas, express their opinion and they can practice it in daily life. Whereas some students gave negative perceptions toward the media used by English teachers in the teaching and learning process that they can not be enthusiastic/spirit to learn English, pronounce the words correctly, find new ideas, and express their opinion because they were lazy, being wary and afraid of being wrong in learning English. This research provides recommendations to English teachers to be more creative in choosing instructional media to be used when teaching English.